Peningkatan Produksi dan Perbaikan Pemasaran dari Produk Abon Cakalang Pedas Kedai Shafa di kelurahan Pandang, Panakkukang, Makassar - Sukmawati Sukmawati; Ira Asmaliani; Ajmal As'ad (I-Com: Indonesian Community Journal, 2024)
Skipjack tuna (Katsuwonus pelamis) is a superior fishery commodity with high economic value in South Sulawesi. Skipjack tuna has a high nutritional content, such as protein, omega 3 and vitamins, so it can be used as processed shredded meat. This service aims to increase the production of one of the home industries, namely Kedai Shafa, by improving the nutritional quality of shredded products by adding banana bud as a vegetable source. Apart from that, improving marketing and service quality can increase sales of shredded meat. Banana bud are a source of protein which can protect the heart because act as antioxidant. The target partners for this service are 12 people and include economically productive community groups. This activity was carried out using Community Development, educational, persuasive and participatory methods. The result was an increase in partner knowledge by 85 – 95% regarding the benefits of skipjack floss combined with banana blossom, use of tools and marketing strategies. Apart from that, this service activity also produced a product innovation, namely shredded skipjack tuna with the addition of banana blossoms which are beneficial for health